2022
DOI: 10.3389/fvets.2022.932587
|View full text |Cite
|
Sign up to set email alerts
|

Craniomaxillofacial trauma in immature dogs–etiology, treatments, and outcomes

Abstract: Treatment of craniomaxillofacial (CMF) trauma in dogs often requires a multidisciplinary approach and a thorough understanding of the CMF anatomical structures involved. This retrospective study aimed to utilize computed tomography (CT) studies of immature dogs evaluated for CMF trauma and to describe common fracture locations, treatment modalities, and complications, as well as the fracture healing outcomes. The medical records and CT studies of 94 dogs under 1 year of age over a 13-year period were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Untreated, it may lead to asymmetrical mandibular growth and the inability to open the mouth (43). A previous study on 94 immature dogs with craniomaxillofacial trauma found that 36.2% had TMJ articular surface fractures, but none developed intraarticular ankylosis, and 10.3% developed extraarticular ankylosis (44). In our case series of four dogs undergoing condylectomy and caudal mandibulectomy, no patient experienced intraarticular or extraarticular ankylosis, reinforcing the rarity of these complications following TMJ trauma demonstrated in this report.…”
Section: Discussionsupporting
confidence: 85%
“…Untreated, it may lead to asymmetrical mandibular growth and the inability to open the mouth (43). A previous study on 94 immature dogs with craniomaxillofacial trauma found that 36.2% had TMJ articular surface fractures, but none developed intraarticular ankylosis, and 10.3% developed extraarticular ankylosis (44). In our case series of four dogs undergoing condylectomy and caudal mandibulectomy, no patient experienced intraarticular or extraarticular ankylosis, reinforcing the rarity of these complications following TMJ trauma demonstrated in this report.…”
Section: Discussionsupporting
confidence: 85%
“…However, 3DVR images of TMJs are only briefly included when studying CT scans of different TMJ pathologies [6,[23][24][25]. Moreover, in specific works about TMJ, only lateral, rostrolateral [6,[25][26][27] and ventral images [27] of TMJ were superficially shown. No detailed studies of the medial, ventral, ventrolateral and caudoventral aspects of the TMJ and its relationship with other bone structures were found to employ 3DVR images.…”
Section: Introductionmentioning
confidence: 99%